The Association of Urinary Sodium and Potassium with Renal Uric Acid Excretion in Patients with Chronic Kidney Disease - Fengqin Li; Hui Guo; Jianan Zou; Weijun Chen; Yijun Lu; Xiaoli Zhang; Chensheng Fu; Jing Xiao; Zhibin Ye (Karger Publishers, 2018)
Background/Aims: Hypertension and hyperuricemia are closely associated with an intermingled cause and effect relationship. Additionally, urinary sodium and potassium excretion is related to blood pressure. Whether or not it is associated with urinary uric acid excretion is not clear. Therefore, we aim to study the association of urinary sodium and potassium with renal uric acid excretion in patients with CKD. Methods: A cross-sectional study of 428 patients with CKD recruited from our department was conducted. All patients were divided into hypertension and non-hypertension group. In these two groups, Spearman correlation and multiple linear regression analysis were used to study the correlation of urinary sodium and potassium with renal handling of uric acid. Results: According to multiple linear regression analysis, in hypertension group, fractional excretion of sodium (FEna) was negatively correlated with 24 hour urinary uric acid (24-hUur) and uric acid clearance rate (Cur) (beta coefficients [B]=-0.066, -0.182, respectively; both P< 0.05), and positively correlated with fractional excretion of uric acid (FEur) (B=1.641, P< 0.001). Additionally, fractional excretion of potassium (FEk) was positively correlated with FEur (B=0.576, P< 0.001), but not related to 24-hUur and Cur (both P>0.05). And urinary sodium/potassium ratio (Una/k) was negatively related to 24-h Uur and Cur (B=-0.047, -0.159, both P< 0.05), and positively related to FEur (B=0.578, P< 0.05). Furthermore, FEna and FEk was still positively related to FEur in the lowest tertile of eGFR groups (both P< 0.05), but not related in the second and highest tertile of eGFR groups (all P> 0.05). In non-hypertension group, FEna was negatively correlated with 24-hUur (B=-0.589, P< 0.05), but not related to Cur and FEur (both P> 0.05). both FEk and Una/k was not related to 24-h Uur, Cur and FEur (all P> 0.05). Moreover, FEna and FEk was still not correlated with FEur in all tertiles of eGFR groups (all P> 0.05). Conclusion: We found that in patients with CKD, urinary sodium and potassium excretion is closely correlated to renal handling of uric acid, which was pronounced in hypertensive patients with low eGFR. This phenomenon may be one of the mechanisms of the relationship between hypertension and hyperuricemia. Further research is needed to confirm it. It is expected to manage hyperuricemia in terms of controlling the diet of sodium and potassium.